2022
DOI: 10.3390/rs14246267
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Solution of UAV Push-Broom Hyperspectral System Based on Geometric Correction with MSI and Radiation Correction Considering Outdoor Illumination Variation

Abstract: The unmanned aerial vehicle (UAV)-borne hyperspectral imaging system has the advantages of high spatial resolution, flexible operation, under-cloud flying, and easy cooperation with ground synchronous tests. Because this platform often flies under clouds, variations in solar illumination lead to irradiance inconsistency between different rows of hyperspectral images (HSIs). This inconsistency causes errors in radiation correction. In addition, due to the accuracy limitations of the GPS/inertial measurement uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Also, ensuring accurate spectral calibration across different bands is essential, but can be challenging due to variations in sensor characteristics and environmental conditions [9]. Additionally, achieving precise geometric correction to align images with ground truth data or other spatial datasets can be difficult, particularly in dynamic environments with factors such as UAV motion and terrain variations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, ensuring accurate spectral calibration across different bands is essential, but can be challenging due to variations in sensor characteristics and environmental conditions [9]. Additionally, achieving precise geometric correction to align images with ground truth data or other spatial datasets can be difficult, particularly in dynamic environments with factors such as UAV motion and terrain variations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a slight error compared to the actual value. Latini et al [12] demonstrated the consistency of the vegetation spectral dimensions by using a UAV to collect vegetation data at 90 m altitude and modeling the comparison of the BRDF with Sentinel satellite data. Still, the number of acquired images was small, and the illumination effect was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Still, acquiring images that consider spectral accuracy, spatial resolution, and spectral resolution simultaneously is challenging. Hovering imaging is not possible when using push-broom imaging, and the UAV must be controlled to push-broom along a straight line at a uniform speed to acquire multi-angle information [12]. Push-broom imagers have high signal-to-noise ratios (SNRs) and high spectral resolutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation